Answer: ![A^{-1}=\left[\begin{array}{cc}\frac{3}{2}&-\frac{1}{2}\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=A%5E%7B-1%7D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B3%7D%7B2%7D%26-%5Cfrac%7B1%7D%7B2%7D%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
<u>Step-by-step explanation:</u>
![\left[\begin{array}{cc}2&1\\4&3\end{array}\right]=\left[\begin{array}{cc}1&0\\0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D2%261%5C%5C4%263%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D)
![\dfrac{1}{2}Row\ 1\rightarrow\left[\begin{array}{cc}1&\frac{1}{2}\\4&3\end{array}\right]=\left[\begin{array}{cc}\frac{1}{2}&0\\0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7DRow%5C%201%5Crightarrow%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%26%5Cfrac%7B1%7D%7B2%7D%5C%5C4%263%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B1%7D%7B2%7D%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D)
![Row\ 2 -4 \ Row\ 1\rightarrow \left[\begin{array}{cc}1&\frac{1}{2}\\0&1\end{array}\right]=\left[\begin{array}{cc}\frac{1}{2}&0\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=Row%5C%202%20-4%20%5C%20Row%5C%201%5Crightarrow%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%26%5Cfrac%7B1%7D%7B2%7D%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B1%7D%7B2%7D%260%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
![Row\ 1-\dfrac{1}{2}\ Row\ 2 \rightarrow \left[\begin{array}{cc}1&0\\0&1\end{array}\right]=\left[\begin{array}{cc}\frac{3}{2}&-\frac{1}{2}\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=Row%5C%201-%5Cdfrac%7B1%7D%7B2%7D%5C%20Row%5C%202%20%5Crightarrow%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B3%7D%7B2%7D%26-%5Cfrac%7B1%7D%7B2%7D%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
Step-by-step explanation:
I have no idea if I'm doing it right but my guess would be to take the values that we get from f(x) and g(x) when x = 1. Therefore we get that f(x) is equal to 4 and g(x) is equal to -1. We than just do f/g which is 4/-1 which gives us the final answer of -4 which is option B.
Answer: Option B, -4
Answer:
x=27
Step-by-step explanation:
expanding the above expression we get
5x+5=4x+32
grouping numbers with coefficient of x at the left side and constant at the right side we get
5x-4x=32-5
x=27
Answer:
x=2
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2x−1−1=x−3−(−5+x)
2x−1−1=x−3+−1(−5+x)(Distribute the Negative Sign)
2x−1−1=x+−3+(−1)(−5)+−1x
2x−1−1=x+−3+5+−x
2x+−1+−1=x+−3+5+−x
(2x)+(−1+−1)=(x+−x)+(−3+5)(Combine Like Terms)
2x+−2=2
2x−2=2
Step 2: Add 2 to both sides.
2x−2+2=2+2
2x=4
Step 3: Divide both sides by 2.
2x
2
=
4
2
x=2